2019
DOI: 10.1111/nph.16264
|View full text |Cite
|
Sign up to set email alerts
|

Low phosphate represses histone deacetylase complex1 to regulate root system architecture remodeling in Arabidopsis

Abstract: The mechanisms involved in the regulation of gene expression in response to phosphate (Pi) deficiency have been extensively studied, but their chromatin-level regulation remains poorly understood.We examined the role of histone acetylation in response to Pi deficiency by using the histone deacetylase complex1 (hdc1) mutant. Genes involved in root system architecture (RSA) remodeling were analyzed by quantitative real-time polymerase chain reaction (qPCR) and chromatin immunoprecipitation qPCR.We demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Chromatin immunoprecipitation assay was conducted as described previously (Xu et al, 2020). Briefly, approximately 1.5 g root tissues were cross‐linked with 1% formaldehyde, and then the nuclei were isolated and lysed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin immunoprecipitation assay was conducted as described previously (Xu et al, 2020). Briefly, approximately 1.5 g root tissues were cross‐linked with 1% formaldehyde, and then the nuclei were isolated and lysed.…”
Section: Methodsmentioning
confidence: 99%
“…Root elongation of seedlings treated with and without Al was measured using a ruler and the relative root elongation was calculated to assess Al resistance. Low Pi treatment was conducted as previously described (Xu et al, 2020). Briefly, seeds were sowed on the low Pi medium supplemented with 10 μmol/L Pi (−Pi) and the high Pi medium containing 625 μmol/L Pi (+Pi).…”
Section: Plant Culture and Treatmentmentioning
confidence: 99%
“…Furthermore, it was demonstrated that up to 40% of rice genes undergo chromatin state changes in response to low Pi availability and that genes that are differentially expressed in response to Pi limitation are overrepresented in this set of genes with low-Pi activated chromatin dynamics (Foroozani et al 2020). Another chromatin modi cation, histone deacetylation, was recently shown to repress the transcriptional activation of genes related to the modi cation of root architecture in response to low Pi in Arabidopsis (Xu et al 2020). Altogether, recent evidence highlights the importance of epigenetic regulation on plant adaptation to low Pi availability and its value as the foundation for the development of innovative genome manipulation tools that might enable breeders to produce low-Pi tolerant crops (Figure 5).…”
Section: Regulation Mechanisms By Inositol Polyphosphate Sensingmentioning
confidence: 99%
“…19,37 Concomitantly, under P sufficient conditions the HISTONE DEACETYLASE COMPLEX 1 (HDC1) protein directly acts as a repressor of genes involved in P starvationrelated remodeling of the root system architecture. 18 When the root system encounters P starvation, HDC1 protein levels are reduced by probable proteasome-mediated degradation, leading to the up-regulation of genes involved in root system architecture remodeling. Altogether, these discoveries show the importance of dynamic histone active and repressive marks enrichment to respond to P starvation.…”
Section: P Starvation Response Is Controlled By Multiple Chromatimentioning
confidence: 99%